METAPHOR IN BAHASA BATAK ANGKOLA JULU PROVERB - Lenni Marlina Harahap; Sri Minda Murni; Sumarsih . Sumarsih (LINGUISTIK TERAPAN, 2022)
Discussion of metaphor is also widely associated with proverbs. This is not surprising because metaphor is a part of figure of speech in literary theory. The aim of this research was to find out the reasons of metaphor realized in BBAJ Proverb in the way they are. Thinking and creating metaphors that human cannot escape from their environtment, because they always interact with it. The study of interactions between humans and their environment (animate and inanimate beings) is called an ecological study systemThe data sources of this research were 5 people. They are the descendants of native speakers who first lived in the village of Sabungan Julu. The research is a kind of qualitative descriptive. The data of the research focus on phrase, which contain of metaphor on BBAJ Proverb, the technique of collecting data that is used in the research is collecting or listing proverbs from Bahasa Batak Angkola Julu. From some process of communication the researcher has been listed any proverbs based on the context of interaction and communication. The results of this research as the reason of the using metaphor, the BBAJ’s Proverb used depends on the social and cultural environtment shows their identity . Results of the reason of using metaphor in BBAJ Proverb are, the microsmos reason is the most prominent reason where the percentage distribution is 52,5% while the macrocosmos reason is 47,5 %. There  is a proverb which has two reason of using metaphor in BBAJ Proverb, both macrocosmos and microsmos. The proverb is halak na lilu di alaman /pae sobanan.  From the result it can be concluded that the reason for the creation of metaphors in BBAJ Proverb is more dominated by the culture, customs, mindset and habits of the Angkola Julu people themselves (microcosmos) rather than the geographical conditions of their natural environment (macrocosmos). Keywords: Metaphor, Bahasa Batak Angkola Julu (BBAJ) Proverb, the Reason of the Using Metaphor